Perancangan Sistem Informasi Akuntansi Penjualan dan Persediaan Barang Dagang dengan Excel Macro di Toko Surya - Ayu Amelia Putri; Fatma Ginoga, Lesia (Account: Jurnal Akuntansi, Keuangan dan Perbankan, 2024)
Management of sales and inventory requires relevant and accurate information for appropriate decision-making. However, many MSMEs have not implemented computerized accounting information systems and neglect inventory and sales recording. At Toko Surya, incoming goods and sales are not yet computerized, and there are no detailed records. The recommended solution is to design an accounting information system for sales and inventory using Excel Macro. The purpose of this final project is to describe the sales and inventory system applied at Toko Surya and to design an Excel Macro-based system. Data collection methods include interviews, observation, documentation, and literature study, using the waterfall model. The sales and inventory system at Toko Surya encompasses functions, records, documents, and procedures that are still manual and simple. The design includes system functions and requirements, data flow diagrams, and input and output designs. After system testing, the designed Excel Macro-based system has the potential to provide solutions to the problems at Toko Surya.